Determination of Anthocyanin Levels in Saffron Flower (Crocus sativus L) Infusion with Differential pH Method - Fitriyani, Fitriyani; Nugraha, Davit (LPPM STIKes Muhammadiyah Ciamis, 2024)
Saffron (Crocus sativus L), as an important herbal plant in medicine, cosmetics and ather health industries. Saffron (Crocus sativus L) is used in tradisional medicine to treat various types of diseases, including to trear chronic diseases such as asthma and artritis, also used to treat coughs and fevers. The saffron plant (Crocus sativus L) contains active compounds, namely, carotenoids, anthocyanins, vitamins (tiboflavin and thiamine), and minerals. The purpose of this study was to determine the levels of anthocyanins in saffron flowers (Crocus sativus L). anthocyanins are a group of pigments that cause a reddish color, found in water-soluble cell fluids. Anthocyanin compounds function as antioxidants and free radical scavengers, thus playing a role in preventing aging, cancer, and degenerative diseases. The results of data analysis show that all the average levels of steeping saffron flowers from each temperature are different, in other words the average levels of steeping levels of saffron flowers from each temperature there are significant differences.